Analisis Faktor Pendorong Niat Menggunakan Aplikasi PeduliLindungi Menggunakan Model UTAUT Modifikasi - Nurisa Rahma Shantika; Tri Lathif Mardi Suryanto; Arista Pratama (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
In 2020, the world is faced with the sudden presence of the Covid-19 virus which spreads rapidly among people who are in close contact. To control and limit the spread of the virus infection, a mobile health application (mHealth) as a technology-based approach has been used. Contact tracing application is one kind of mHealth system that is capable and suitable for this kind of situation. Many countries have implemented the adoption of contact tracing applications during the pandemic, Indonesia is no exception, it is called Aplikasi PeduliLindungi. The existence of contact tracing application such as Aplikasi PeduliLindungi is considered to be very helpful. Therefore, research related to Aplikasi PeduliLindungi is considered necessary, because contact tracing applications are considered as one of the important steps to cut down the spread of the virus. Investigating factors that can influence the intention to adopt a contact tracing application is highly necessary, since the effectiveness of implementing a Covid-19 contact tracing application relies on the public’s willingness to use the application. To discover the factors that could influence intention of the users to use a new technology, an analysis can be carried out using the UTAUT model. The results is that the factors that significantly influence the intention of the users to use Aplikasi PeduliLindungi are Performance Expectancy, Facilitating Conditions, and Covid-19-related Stress. Meanwhile, Effort Expectancy, Social Influence, Innovativeness, and App-related Privacy Concern were found to have no significant effect on users' intention to use Aplikasi PeduliLindungi.